Eco-friendly gelatin/rice bran polysaccharides packaging films for fruit preservation - Wei Wang; Xiaoju Chen; Xinyu Ye; Bei Ni; Lin Xu; Minmin Chen (Materials Letters: X, 2025)
Rice bran polysaccharides (RB) has a wide range of biological activities. However, it is rarely investigated as a food packaging material. The present study aimed to extract RB and prepare gelatin/RB (Ge/RB) film by solution casting method. The results indicated the incorporation of RB into films increased the roughness, tensile strength, and antioxidant activity but decreased the water contact angle of the films. In addition, the film could decrease the weight loss rate of the apple and prevent wound decay of the pear. Therefore, the Ge/RB food packaging film has great potential for food preservation.